Comparative effectiveness of statin therapy in patients with hypertension of high and very high cardiovascular risk in actual clinical practice in Irkutsk - O. A. Ivanova; S. G. Kuklin; S. S. Sizova; T. A. Novoselova; L. R. Gaifullina (Кардиоваскулярная терапия и профилактика, 2021)
Aim. To study lipid-lowering therapy in patients with high and very high risk of cardiovascular events (CVEs) at the outpatient and inpatient care stages in Irkutsk.Material and methods. We analyzed 260 discharge summaries of patients with hypertension of high and very high risk of CVEs for the second half of 2019: 145  — from a hospital; 115  — from outpatient records. Patient adherence to statin therapy, achievement of target lowdensity lipoprotein cholesterol (LDL-C) levels in each patient subgroup was assessed.Results. The proportion of patients who reached the recommended LDL-C levels in accordance with the 2017 guidelines tends to increase in comparison with prior data. High adherence to lipid-lowering therapy was accompanied by an increase in the proportion of patients reaching the recommended LDL-C levels. In most cases, regardless of cardiovascular risk, low-dose statin therapy were used. A detailed analysis of adherence to statin therapy using questionnaires revealed that more than half of patients in high-risk categories (64%) did not comply with lipid-lowering therapy.Conclusion. Favorable trends were revealed in relation to an increase in the proportion of high-risk patients reaching target LDL-C levels. Adherence to statin therapy remains low. Previously established problems in managing such patients remains: stereotyped lipid-lowering therapy prescriptions without taking into account cardiovascular risk, the use of low-dose therapy, and the frequent prescription of statins with a lower lipid-lowering effect. Inpatients use higher statin doses than outpatients.